Late Mortality, Subsequent Malignant Neoplasms and Hospitalisations in Long-Term Survivors of Adolescent and Young Adult Hematological Cancers - Trama, Annalisa; Vener, Claudia; Lasalvia, Paolo; Bernasconi, Alice; , the Ada Working Group; Zorzi, Manuel; Andreano, Anita; Contiero, Paolo; Manneschi, Gianfranco; Falcini, Fabio; Castaing, Marine; Filiberti, Rosa Angela; et al. (Frontiers in Oncology, 2022)
Background: Increased success in the treatment of haematological cancers contributed to the increase of 5-year survival for most adolescent and young adults (AYAs) with these tumours. However, as 5-year survival increased, it became clear that AYA long-term survivors were at increased risk for severe late effects. Moreover, limited information on long-term cancer impact is available for AYA, since most studies focused on children and adolescents. We aimed to assess various long-term outcomes on AYA survivors of haematological cancers. Methods: We selected patients diagnosed with a first primary haematological cancer between 1997 and 2006, in the Italian nationwide population-based cohort of AYA cancer survivors (i.e. alive at least 5 years after cancer diagnosis). Long-term outcomes of interest were: second malignant neoplasms (SMNs), hospitalisations and overall mortality. We calculated standardized incidence ratios (SIRs), standardised hospitalisation rate ratios (SHRs) and standardised mortality rate ratios (SMRs). To study morbidity patterns over time, we modeled observed incidence rates by fitting flexible parametric models for non linear patterns and we used linear regression for linear patterns. Results: The study cohort included 5,042 AYA haematological cancer survivors of which 1,237 and 3,805 had a leukaemia and lymphoma diagnosis, respectively. AYA survivors were at substantially increased risk for SMN (SIR=2.1; 95%CI=1.7; 2.6), hospitalisation (SHR=1.5; 95%CI=1.5; 1.6), and mortality (SMR=1.4; 95%CI=1.2; 1.6) with differences between leukaemia and lymphoma survivors. The highest excess risks of hospitalisations were for infectious diseases, respiratory diseases, and diseases of blood-forming organs. The morbidity pattern differs over time by morbidity type. Conclusions: Our results support the need for strict follow-up plans for survivors, and call for further study to better personalised follow-up plans for AYA cancer survivors.